2023
DOI: 10.1002/cpt.3000
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacology and Translational Considerations in the Development of CRISPR‐Based Therapies

Abstract: Genome editing holds the potential for curative treatments of human disease, however, clinical realization has proven to be a challenging journey with incremental progress made up until recently. Over the last decade, advances in clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR‐associated protein (Cas) systems have provided the necessary breakthrough for genome editing in the clinic. The progress of investigational CRISPR therapies from bench to bedside reflects the culmination of mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…We next attempted to identify mechanisms contributing to potential second peak in mRNA PK and its implication for PD response. LNP redistribution and recycling have been observed in LNP based therapies (Goel et al, 2020;Abdelhady et al, 2023) and the model provided a platform to study this effect in silico given the absence of mechanistic empirical data. Simulations indicated that this second peak is formed under fast recycling rates and slow reuptake rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We next attempted to identify mechanisms contributing to potential second peak in mRNA PK and its implication for PD response. LNP redistribution and recycling have been observed in LNP based therapies (Goel et al, 2020;Abdelhady et al, 2023) and the model provided a platform to study this effect in silico given the absence of mechanistic empirical data. Simulations indicated that this second peak is formed under fast recycling rates and slow reuptake rates.…”
Section: Discussionmentioning
confidence: 99%
“…The model also incorporates the recycling mechanism of mRNA loaded LNP to explore the impact of redistribution on PK dynamics. This model allows for in silico investigation of conditions necessary for generation of a second peak in mRNA PK as observed experimentally (Goel et al, 2020;Abdelhady et al, 2023). Simulations also show implications of the recycling on protein production within the context of a nonsecreted intracellular enzyme such as UGT.…”
mentioning
confidence: 90%
“…The unique mechanism of action of CRISPR therapy requires new approaches for clinical translation and dose selection. Abdelhady and colleagues review the current status of clinical pharmacology and translation in the CRISPR field, with an emphasis on a mechanistic, quantitative approach to address the uncertainties from other empirical approaches in clinical development and study design 23 …”
Section: Figurementioning
confidence: 99%
“…Abdelhady and colleagues review the current status of clinical pharmacology and translation in the CRISPR field, with an emphasis on a mechanistic, quantitative approach to address the uncertainties from other empirical approaches in clinical development and study design. 23 Physiologically-based PK (PBPK) and quantitative systems pharmacology (QSP) modeling approaches are also evolving to support development of novel modalities. Parra-Guillen et al 24 describe the development and application of a mechanistic PBPK model linked to tumor response to assess clinical response to an oncolytic virus.…”
mentioning
confidence: 99%